Effect of process parameters on aqueous extraction of thymol and other phytonutrients from herbal seed Ajwain (Trachyspermum ammi L.) - Jain, Amit; Sengupta, Sourav; De, Sirshendu (Journal of applied research on medicinal and aromatic plants, 2018)
•Aqueous extraction of phytonutrients from ajwain is reported.•Optimum extraction conditions are evaluated to produce a marketable product.•Optimum conditions: seed to water ratio: 0.30 g/mL, time:16 min, temperature:52 °C.•Eigenvalue analysis confirms the presence of global maximum.•2.1mg of thymol per kg of ajwain seeds is extracted at optimum conditions. Ajwain (Trachyspermum ammi L.) is a therapeutic herbal spice with many benefits and a good source of phytonutrients. The optimum process conditions were evaluated for aqueous extraction of phytonutrients from ajwain. Seed to water ratio (0.25 to 1 g/mL), extraction time (10 to 60 min) and extraction temperature (30 °C to 60 °C) were selected as independent variables and their effects on the concentration of protein, thymol, total solids and antioxidant activity were examined. The linear and combined effects of independent process variables on quality parameters were analyzed by response surface methodology. The second-order polynomial model was generated by analysis of variance for each response and its significance and adequacy were judged statistically by the coefficient of determination, the coefficient of variance, lack of fit test and adequate precision. Numerical optimization was carried out to evaluate the optimum operating conditions subject to maximum thymol concentration and antioxidant activity and minimum concentration of protein and total solids, and optimum conditions evaluated as: seed to water ratio: 0.30 g/mL, extraction time: 16 min and extraction temperature: 52 °C. At the optimal conditions, 2.1 mg of thymol was extracted per kg of ajwain seeds. Eigenvalue analysis was also undertaken to corroborate the findings from numerical optimization. The numerically optimized result was validated with experimental results by conducting a separate set of experiments and observed that the experimental results are within the range of ±10% of the generated numerical optimization results, thereby confirming the optimum conditions.